'Do larger molars and robust jaws in early hominins represent dietary adaptation?' A New Study in Tooth Wear. Issue 1 (24th October 2013) - Clement, Anna; Hillson, Simon
Abstract : Diet imposes significant constraints on the biology and behaviour of animals. The fossil record suggests that key changes in diet have taken place throughout the course of human evolution. Defining these changes enables us to understand the behaviour of our extinct fossil ancestors. Several lines of evidence are available for studying the diet of early hominins, including craniodental morphology, palaeoecology, dental microwear and stable isotopes. They do, however, often provide conflicting results. Using dental macrowear analysis, this new UCL Institute of Archaeology project will provide an alternative source of information on early hominin diet. Dental macrowear has often been used to analyse diet in archaeological populations, but this will be the first time that this type of detailed study has been applied to the early hominin fossil record.